Regulasi Nikah Beda Agama Dalam Sema Nomor 2 Tahun 2023 : Perspektif Maqāṣid al-Syarī‘ah Ibn ‘Āsyūr - Misbahul Huda; Ida Rif’atus Sa’adah; Baihaqi, Achmad (Al-Syakhsiyyah: Journal of Law and Family Studies, 2024)
In 2023 the Supreme Court issued Supreme Court Circular Letter (SEMA) Number 2 of 2023 concerning Instructions for Judges in Adjudicating Cases on Applications for Registration of Marriages Between People of Different Religions and Beliefs . SEMA sparked a polemic because it was considered discriminatory and lacked urgency. This research was conducted to explore the actual regulations for interfaith marriages in SEMA Number 2 of 2023 from the perspective of MaqÄá¹£id SyarÄ«'ah Ibnu 'Ä€syÅ«r. In an effort to answer the perceived discriminatory policies contained in SEMA Number 2 of 2023 the author uses 4 bases of Ibn Asyur's MaqÄá¹£id asy-SyarÄ«'ah. The concept of MaqÄá¹£id ash-SyarÄ«'ah 'Ammah and Ibn Asyur's level of Maslahah will be used to formulate and track the level of urgency in promulgating SEMA Number 2 of 2023 through the benefits contained therein. In this process the author will use the statute approach and conceptual approach, with descriptive analysis. The research results show that the urgency of promulgating SEMA Number 2 of 2023 in the Indonesian context, according to the author, is at the level of hajiyat benefits . Meanwhile, efforts to enforce or supremacy of law through SEMA Number 2 of 2023 will be less effective. Apart from that, SEMA Number 2 of 2023 is considered to be less than fully successful in providing social stability and resilience to the justice-seeking community as desired by Ibnu Asyur through legal supremacy efforts.